Combining TerraSAR-X and time-lapse photography for seasonal sea ice monitoring: the case of Deception Bay, Nunavik - Dufour-Beauséjour, Sophie; Wendleder, Anna; Gauthier, Yves; Bernier, Monique; Poulin, Jimmy; Gilbert, Veronique; Tuniq, Juupi; Rouleau, Amélie; Roth, Achim (The Cryosphere, 2020)
Inuit have reported greater inter-annual variability in seasonal sea ice conditions. For Deception Bay (Nunavik), an area prized for seal and caribou hunting, an increase in solid precipitation and a shorter snow cover period is expected in the near future. In this context, and considering ice-breaking transport in the fjord by mining companies, we monitored sea ice in the area for three seasons of ice between 2015 and 2018. This article presents a case study for the combined use of TerraSAR- X and time-lapse photography time-series in order to monitor snow-covered sea ice seasonal processes. The X-band median backscattering is shown to reproduce the seasonal evolution expected from C-band data. Two different freeze-up and breakup processes are characterized. New X-band backscattering values from newly formed ice types are reported. The monitoring approach presented in this article has the potential to be applied in other remote locations, and processes outlined here may inform our understanding of other fjords or bays where ice-breakers transit.